2014
DOI: 10.1177/1757975914552914
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a school-based nutrition and food safety education program among primary and junior high school students in Chongqing, China

Abstract: Abstract:Background: Health behavioral patterns, especially eating patterns, established in childhood often carry over into adulthood, and some of the unhealthy ones are later associated with adult morbidity and mortality. Recently, a few nutrition and food safety education programs have been implemented in primary and junior high schools in China. Purpose: This study aims to examine the effectiveness of a school-based nutrition and food safety education program among primary and junior high school students in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 42 publications
8
36
0
Order By: Relevance
“…An Australian study of consumers’ food safety knowledge indicated poor safety knowledge was negatively associated with health education at school 12 . International studies have also reported positive effects of school‐based nutrition and food safety education on students’ knowledge and behaviour 36,37 . In addition, the important role of parents’ knowledge and behaviour on their children's understanding and practices of N&Fs related issues identified in the current study has also been reported in international studies on the (positive) influence of parents as role models for healthy eating behaviour among teenagers 38 and middle school students 39 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…An Australian study of consumers’ food safety knowledge indicated poor safety knowledge was negatively associated with health education at school 12 . International studies have also reported positive effects of school‐based nutrition and food safety education on students’ knowledge and behaviour 36,37 . In addition, the important role of parents’ knowledge and behaviour on their children's understanding and practices of N&Fs related issues identified in the current study has also been reported in international studies on the (positive) influence of parents as role models for healthy eating behaviour among teenagers 38 and middle school students 39 .…”
Section: Discussionsupporting
confidence: 73%
“…12 International studies have also reported positive effects of schoolbased nutrition and food safety education on students' knowledge and behaviour. 36,37 In addition, the important role of parents' knowledge and behaviour on their children's understanding and practices of N&Fs related issues identified in the current study has also been reported in international studies on the (positive) influence of parents as role models for healthy eating behaviour among teenagers 38 and middle school students. 39 This reinforces the need to consider nutrition education in a wider context than just what may or may not occur in schools and the need to explore the potential to promote important N&FS topics within the supportive environment of the family.…”
Section: Discussionsupporting
confidence: 71%
“…The education about food safety and nutrition among school students were a great impact on the student's nutrition knowledge in school. The educational program about nutrition and food safety was very beneficial and effective for school students, and the health education about nutrition and food safety to be applicable, practicable, and improve the health (Zhou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Middle school appears to be the ideal time to educate students on new topics such as food processing and systems as they are still in the process of developing behaviors that they will retain throughout their lives, as proven evident by research on other subject areas such as nutrition (Zhou et al., 2016) and physical education (Bocarro, Kanters, Casper, & Forrester, 2008). Introducing middle schoolers to ideas related to food processing and food systems may allow for the development of positive behaviors associated with these topics (Richards et al., 2008).…”
Section: Introductionmentioning
confidence: 99%